Chapter 23 Voices and Visions: Mind, Body and Affect in Medieval Writing - Richards, Jennifer; Atkinson, Sarah; Macnaughton, Jane (Edinburgh University Press, 2021)
In this landmark Companion, expert contributors from around the world map out the field of the critical medical humanities. This is the first volume to introduce comprehensively the ways in which interdisciplinary thinking across the humanities and social sciences might contribute to, critique and develop medical understanding of the human individually and collectively. The thirty-six newly commissioned chapters range widely within and across disciplinary fields, always alert to the intersections between medicine, as broadly defined, and critical thinking. Each chapter offers suggestions for further reading on the issues raised, and each section concludes with an Afterword, written by a leading critic, outlining future possibilities for cutting-edge work in this area. Topics covered in this volume include: the affective body, biomedicine, blindness, breath, disability, early modern medical practice, fatness, the genome, language, madness, narrative, race, systems biology, performance, the postcolonial, public health, touch, twins, voice and wonder.